Correlations of the growth indexes and yield of winter wheat in a long-term experiment - Vári, Enikő (Acta Agraria Debreceniensis, 2014)
The experiments were carried out at the Látókép experimental station of the Centre for Agricultural Sciences of University of Debrecen on chernozem soil in a long term winter wheat experiment. As forecrop rotation, we set up two models: a biculture (wheat and corn) and a triculture (pea, wheat and corn). We applied three levels of nutrients during the fertilization process (control, N50P35K40 and N150P105K120). The third variable studied was irrigation in case of which we tested non-irrigated variables (Ö1) and irrigation variables complemented up to the optimum (Ö3). The effect of pre-crops, irrigation and nutrient-supply levels on some growth-parameters (LAI, LAD), weight of dry matter, just as SPADvalues and yield amounts of winter wheat has been investigated in this experiment. We tried to find out the extent of relationship between the different parameters, and we used the correlation analysis. The correlation analyses have confirmed that all of the investigated parameters had almost in all cases close positive correlation to the yield amount. These results have confirmed that the leaf area, the leaf duration, the SPADvalues, the fertilization and the forecrop have altogether resulted in the production of maximum grain yields.